Melacak Dakwah Keilmuan Ulama Nusantara: Geliat Pergerakan KH. Hasyim Asy'ari - Luthfi Maulana (IQTIDA : Journal of Da'wah and Communication, 2021)
The da'wah movement in Nusantara inseparable from the scientific stretching of the scholars in bringing Islamic teachings to Nusantara. The teachings of da'wah brought by the scholars are packaged in various ways according to their respective patterns and tendencies. In Java KH. Hasyim Asyari brought preaching treatises with various things, including those related to the teachings of jihad fi sabilillah (jihad resolution), because of the conditions at that time, Indonesia was under Dutch colonial rule, in another context the scientific teachings brought by KH. Asyari is inseparable from his madhzab background as a Sunni, so he brings religious teachings with tawassut (the middle way). In da'wah in the field of education, KH. Hasyim Asy'ari tends to remind the importance of adab and morals as a path for people. In other fields, he also used his scientific credibility to invite Muslims in Indonesia to return to the right path, as was his effort in compiling collections of hadith books as guidelines for the Indonesian Muslim community at that time.